Toward Trust as Result. A Transdisciplinary Research Agenda for the ‘Future of the Internet’ - Stefano De Paoli; GR Gangadharan; Aphra Kerr; Vincenzo D'Andrea (tripleC: Communication, Capitalism & Critique)
Trust has emerged as one of the key challenges for the Future of the Internet and as a key theme of European research. We are convinced that a transdisciplinary research agenda - that we define to as Trust as Result - shared by Sociology and Computer Science, is of paramount importance for devising sustainable Trust solutions for the (Future) Internet stakeholders. The scope of this paper is to present some aspects we consider important for building such an agenda. We distinguish our agenda by comparison with one of the current mainstream interdisciplinary approaches to Trust, that we define to as Trust Modelling and that assumes Trust to be the input of the design of trustworthy ICTs. We propose a different point of view based on the concept of Assemblage as proposed by DeLanda and focus on how we can obtain Trust as the result of the design.